Towards an articulated phenomenological interpretation of architecture phenomenal phenomenology - Shirazi, Mohammad Reza (Routledge research in architecture, 2014)
"This book sheds light on the contemporary status of phenomenological discourse in architecture and investigates its current scholastic as well as practical position. Starting with a concise introduction to the philosophical grounds of phenomenology from the points of view of Husserl, Merleau-Ponty and Heidegger, it presents a critical reading of the works of some leading figures of architectural phenomenology in both theory and practice, such as Christian Norberg-Schultz, Kenneth Frampton, Juhani Pallasmaa, and Steven Holl.Highlighting the main challenges of the current phenomenological discourse in architecture, this book formulates a more articulated method of 'phenomenological interpretation' - dubbed 'phenomenal phenomenology' - as a new and innovative method of interpreting the built environment. Finally, using Tadao Ando's Langen Foundation Museum as a case study, it investigates the architect's contribution to phenomenological discourse, interprets and analyzes the Museum building using the new heuristic method, and thus provides a clear example of its applicability.By introducing a clear, articulated, and practical method of interpretation, this book is of interest to academics and students analyzing and studying architecture and the built environment at various scales. "..